The Impact of Root Temperature on Photosynthesis and Isoprene Emission in Three Different Plant Species. (4th June 2012) - Medori, Mauro; Michelini, Lucia; Nogues, Isabel; Loreto, Francesco; Calfapietra, Carlo
Abstract : Most of the perennial plant species, particularly trees, emit volatile organic compounds (BVOCs) such as isoprene and monoterpenes, which in several cases have been demonstrated to protect against thermal shock and more generally against oxidative stress. In this paper, we show the response of three strong isoprene emitter species, namely, Phragmites australis, Populus x euramericana, and Salix phylicifolia exposed to artificial or natural warming of the root system in different conditions. This aspect has not been investigated so far while it is well known that warming the air around a plant stimulates considerably isoprene emission, as also shown in this paper. In the green house experiments where the warming corresponded with high stress conditions, as confirmed by higher activities of the main antioxidant enzymes, we found that isoprene uncoupled from photosynthesis at a certain stage of the warming treatment and that even when photosynthesis approached to zero isoprene emission was still ongoing. In the field experiment, in a typical cold-limited environment, warming did not affect isoprene emission whereas it increased significantly CO2 assimilation. Our findings suggest that the increase of isoprene could be a good marker of heat stress, whereas the decrease of isoprene a good marker of accelerated foliar senescence, two hypotheses that should be better investigated in the future.